Application of γ‐aminobutyric acid (GABA) and nitrogen regulates aroma biochemistry in fragrant rice. Issue 11 (22nd October 2019) - Xie, Wenjun; Ashraf, Umair; Zhong, Dating; Lin, Rongbin; Xian, Peiqi; Zhao, Tong; Feng, Huoyi; Wang, Shuli; Duan, Meiyang; Tang, Xiangru; Mo, Zhaowen
Abstract: The 2‐acetyl‐1‐pyrroline (2AP) is a key aroma compound in fragrant rice. The present study assessed the γ‐aminobutyric acid (GABA) and nitrogen (N) application induced regulations in the biochemical basis of rice aroma formation. Four N levels, that is, 0, 0.87, 1.75, and 2.61 g/pot, and two GABA treatments, that is, 0 mg/L (GABA0) and 250 mg/L (GABA250), were applied to three fragrant rice cultivars, that is, Yuxiangyouzhan, Yungengyou 14, and Basmati‐385. Results showed that GABA250 increased 2AP, Na, Mn, Zn, and Fe contents by 8.44%, 10.95%, 25.70%, 11.14%, and 43.30%, respectively, under N treatments across cultivars. The GABA250 further enhanced the activities of proline dehydrogenase (PDH), ornithine aminotransferase (OAT) (both at 15 days after heading (d AH), and diamine oxidase (DAO) (at maturity) by 20.36%, 11.24%, and 17.71%, respectively. Significant interaction between GABA and N for Mn, Zn, and Fe contents in grains, proline content in leaves, GABA content in leaves at 15 d AH and maturity stage (MS), Δ1‐pyrroline‐5‐carboxylic acid (P5C) contents in leaves at 15 d AH, and Δ1‐pyrroline‐5‐carboxylate synthase (P5CS), PDH, and OAT activities in leaves at MS was noted. Moreover, the 2AP contents in grains at MS showed a significant and positive correlation with the proline contents in the leaves at 15d AH. In conclusion,  GABA250 enhanced the 2AP, Na, Mn, Zn, and Fe contents, as well as the enzyme activities involved in 2AP biosynthesis. Exogenous GABA and N application improved the 2AP contents and nutrient uptake in fragrant rice. Abstract : GABA250 enhanced the mean values of 2AP, Na, Mn, Zn, and Fe contents, as well as the enzyme activities involved in 2AP biosynthesis. Overall, exogenous GABA and N application improved the 2AP contents and nutrient uptake in fragrant rice.